Pace of shifts in climate regions increases with global temperature - Mahlstein, Irina; Daniel, John S.; Solomon, Susan (Nature climate change, 2013)
This study looks at the pace of change in climate zones as a function of global warming. Using the RCP8.5 scenario, the rate nearly doubles by the end of this century, and about 20% of all land area undergoes a change. In the future, species will have less time to adapt, therefore increasing the risk of extinction. Human-induced climate change causes significant changes in local climates 1 , 2 , which in turn lead to changes in regional climate zones. Large shifts in the world distribution of Köppen–Geiger climate classifications by the end of this century have been projected 3 . However, only a few studies have analysed the pace of these shifts in climate zones 4 , 5 , and none has analysed whether the pace itself changes with increasing global mean temperature. In this study, pace refers to the rate at which climate zones change as a function of amount of global warming. Here we show that present climate projections suggest that the pace of shifting climate zones increases approximately linearly with increasing global temperature. Using the RCP8.5 emissions pathway, the pace nearly doubles by the end of this century and about 20% of all land area undergoes a change in its original climate. This implies that species will have increasingly less time to adapt to Köppen zone changes in the future, which is expected to increase the risk of extinction 5 .